Brain metastases as isolated site of relapse in patients with epithelial ovarian cancer previously treated with platinum and paclitaxel-based chemotherapy. Issue 3 (1st April 2006) - Kastritis, E.; Efstathiou, E.; Gika, D.; Bozas, G.; Koutsoukou, V.; Papadimitriou, C.; Pissakas, G.; Dimopoulos, M. A.; Bamias, A.
Abstract : Brain metastases in patients with epithelial ovarian cancer (EOC) have an estimated incidence of 0.3–1.9% and are isolated in up to 50% of these patients. The risk factors and the prognostic significance of isolated central nervous system (CNS) relapse in patients with EOC who received primary treatment with platinum and paclitaxel have not been identified. We conducted a retrospective study in patients with EOC who relapsed with isolated brain metastases and report our experience. Two hundred sixty-seven patients with stages III and IV EOC, in clinical complete remission after first-line treatment with platinum and paclitaxel, were included in our analysis. After a median follow-up of 65 months, 150 patients had relapsed. Eight patients (5%) had isolated brain metastases. Patient and disease characteristics did not differ among patients who relapsed with isolated brain metastases and those with relapse outside the CNS. Median time to first disease relapse, overall survival, and survival after relapse did not differ significantly between patients with brain metastases and those with relapse outside the CNS. Two patients have died 6 and 12 months after the diagnosis of brain metastases, and 5 patients are alive 4–35 months after the diagnosis of isolated brain metastases. Three patients remain free of disease 4–18 months after treatment with radiotherapy and systemic chemotherapy for their CNS metastatic disease. Patients with isolated brain metastases have comparable survival to patients with relapse outside the CNS, and long-term remission can be achieved in some cases, provided that systemic chemotherapy is added to local treatment.